STRATEGI MARKETING MIX DALAM PERSPEKTIF SYARIAH - Nurcholifah, Ita (Khatulistiwa, 2014)
Business is an activity that requires a serious understanding, ranging from planning what will be made later in the stage of implementation, monitoring, and evaluation. An important step that can be taken by business people is to plan a strategy, so the goal in doing business to gain profit and prosperity can be achieved. One strategy that can be applied in business is the marketing mix strategy. This is a strategy of how to apply 4Ps consisting of product, price, promotion and place. Products created should be halal and needed by society, and product quality is something important for business people to consider. The price of a product has also become a serious matter that should be managed properly to make it reasonable and competitive and free of usury. The promotion is geared to encourage purchases by creating a positive impression of a product that consumers are persuaded to make a purchase without deception. The place can also be defined as the location of the company. The location of a company/business organization should be easily accessible by the public, such as around shopping centres and so forth so as to avoid the interception action by the speculators before marketing. A business person should be able to choose a location that serves to represent the company and can be accessed by the public.